The Effect of Ethanol Ants Nest Extract on Profil Lipid Mice Model Obesity with Type 2 Diabetes - Nuriza, Rizky Alfiqi; Rahardjo, Setyo Sri; Wijayanti, Lilik (Poltekita : Jurnal Ilmu Kesehatan, 2023)
The Ants Nest plant (Myrmecodia pendans) is known to have the potential to reduce blood glucose cholesterol, LDL (Low-Density Lipoprotein), and HDL (High-Density Lipoprotein) in obese patients with Type 2 Diabetes (T2D) because it contains high flavonoid and tannin content that can prevent oxidative stress and inhibit the work of pancreatic β cells, α-glucosidase work, Glut-2, and lipase enzymes. This study aims to study the effect of the management of Ethanol Ants Nest Extract (EANE) on changes in the cholesterol, LDL, and HDL levels of obese rats with T2D. The extraction of the ants nest was carried out using the maceration method with ethanol solvent. Cholesterol, LDL, and HDL values will be obtained through the CHOD PAP. The rats were divided into 6 groups, namely: KNo (standard control), KN (T2D obesity), KP (T2D obesity given metformin), P1, P2, and P3 (T2D obesity given ethanol extract of ant nest 150mg/KgBW/day, 300mg/KgBW/day, and 600mg/KgBW/day for 14 days by gastric sonde). Induction of DM model using streptozocin and nicotinamide. Data were analyzed using Paired T-test and continued by using One-way ANOVA. There was a decrease in cholesterol, LDL, and HDL after 14 days of intervention, which was highest in the P3 group with cholesterol, LDL, and HDL of 64,06 ± 1,97 mg/dl (p < 0.0001), 44,56 ± 2,22 mg/dl (p < 0.0001), and 45,33 ± 2,56 mg/dl (p < 0.0001). The treatment of ethanol extract from ants nest has an effect in reducing cholesterol, LDL, and HDL.